Organisational Commitment, Job Satisfaction and Job Performance Among Operators of Selected Electrical and Electronic Industries in Klang Valley, Malaysia - Ray Lahai, Moses Matthew (1997)
The study was carried out in the industrial areas of Nilai, Ulu Klang and Bangi in Malaysia amongst 426 randomly selected operators in six electronics and electrical industries. The impact of the differential relationships between operators organisational commitment and their job performance was explored using job satisfaction variables in the Herzberg's Two-Factor Motivation theory as intervening variables. Specifically, the objectives of the study were to determine: a) the operators' level of job performance, organisational commitment, satisfaction with the individual facets of job satisfaction, b) the nature of the relationship between the individual facets of job satisfaction (Hygiene and Motivational Factors) and job performance, c) the nature of the relationship between organisational commitment and the individual facets of job satisfaction (Hygiene and Motivator Factors) and the extent to which they can predict organisational commitment. d) whether the Herzberg's Model is a useful framework for the study of intervening factors in the relationship between organisational commitment and job performance. Hypothesised relationships were tested using structured survey responses from the industry workers. hierarchical moderated multiple regression analysis were used to analyse the data. of job performance was measured using performance evaluation scores organisational commitment was measured using the definition of commitment after Mowday et. al. (1982), while their levels of satisfaction with the individual facets of Herzberg'S job satisfaction variables were measured using the items derived from the long form of the Minnesota Satisfaction Questionnaire. Findings of the study revealed that: 1) levels of job performance of the operators was high, 2) the operators level of commitment and overall job satisfaction were related to their job performance, 3) five variables, and administration, inter-personal relationship with supervisor and work itself in the Herzberg's model significantly contributed 27 percent of the variation in organisational commitment. percent of the variance in organisational commitment, 4) the influence of organisational commitment on job performance was mediated by overall job satisfaction. significant interaction effect in the organisational commitment and job performance relationship. advancement and recognition for achievement. 5) the two work related attitudes, organisational commitment and job satisfaction did not appear to be distinct work attitudes. job performance